Pemberdayaan Usaha dan Strategi Pemasaran Produk Melalui Kegiatan Branding pada UMKM Kerajinan Bambu di Kelurahan Kepanjenkidul - Alifah Rizky Wiyanti; Yanda Bara Kusuma (Pusat Riset dan Inovasi Nasional, 2023)
The country of Indonesia is known for its ethnic, religious, and cultural diversity which makes Indonesia have various kinds of arts and crafts. Various typical Indonesian products are created, starting from a large scale such as industry to a small scale, namely UMKMs. The majority of people in Blitar City have their businesses, both in terms of food and beverages, and crafts. Bamboo is one of the plants that live in Indonesia which can be used for various crafts. Bamboo Craft